2005
DOI: 10.1021/ja050148o
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active, Regioselective, and Enantioselective Hydroformylation with Rh Catalysts Ligated by Bis-3,4-diazaphospholanes

Abstract: As with catalytic hydrogenation of alkenes by rhodium complexes, key attributes of rhodium-catalyzed alkene hydroformylation 1 (perfect atom economy, inexpensive reactants, demonstrated performance on industrial scales, readily modified phosphorus ligands) make pursuit of the enantioselective transformation irresistible. Whereas hydrogenation effects net loss of the CdC functional group, hydroformylation results in its transformation to a more versatile functional group, the aldehyde. Although new ligand devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(98 citation statements)
references
References 9 publications
1
96
0
1
Order By: Relevance
“…Among the most effective are (2R,4R)-chiraphite (1) [3] and its analogues, [4] which exhibit enantioselectivities of up to 90 % ee for the hydroformylation of styrene at low temperatures; (R,S)-binaphos (2), [5] which shows high enantioselectivities for the hydroformylation of many structurally diverse olefins; (S,S)-kelliphite (3), which is effective for the hydroformylation of allyl cyanide [6] and vinyl acetate; [7] and (S,S)-esphos (5), which displays a high enantioselectivity for the hydroformylation of vinyl acetate. [8] Together with Landis and co-workers, we recently reported [9] the application of diazaphospholane ligands 4 in AHF reactions which showed outstanding hydroformylation rates and very high enantioselectivities for reactions with styrene and allyl cyanide substrates. Diazaphospholane 4 is especially selective for vinyl acetate at 80 8C (96 % ee, b/l = 35).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Among the most effective are (2R,4R)-chiraphite (1) [3] and its analogues, [4] which exhibit enantioselectivities of up to 90 % ee for the hydroformylation of styrene at low temperatures; (R,S)-binaphos (2), [5] which shows high enantioselectivities for the hydroformylation of many structurally diverse olefins; (S,S)-kelliphite (3), which is effective for the hydroformylation of allyl cyanide [6] and vinyl acetate; [7] and (S,S)-esphos (5), which displays a high enantioselectivity for the hydroformylation of vinyl acetate. [8] Together with Landis and co-workers, we recently reported [9] the application of diazaphospholane ligands 4 in AHF reactions which showed outstanding hydroformylation rates and very high enantioselectivities for reactions with styrene and allyl cyanide substrates. Diazaphospholane 4 is especially selective for vinyl acetate at 80 8C (96 % ee, b/l = 35).…”
mentioning
confidence: 82%
“…The only ligand that shows higher enantioselectivity for the hydroformylation of vinyl acetate is the recently reported diazaphospholane 4 (96 % ee, b/l = 37:1). [9] A second set of hydroformylation reactions was conducted to compare ligand 12 with ligands 1-4 using mixtures of neat olefins at 80 8C and 1.034 MPa pressure of syngas with substrate/catalyst molar ratios of 30 000:1 and a catalyst concentration of 0.062 mm. At these very low catalyst loadings, the rate of hydroformylation with 12 (an average turnover frequency of 4467 h À1 ) was virtually identical to those of 1 and 2 and only slower than 3 and 4 (see Figure 2).…”
mentioning
confidence: 99%
“…[5a] Recently, high regioselectivities and enantioselectivites were reported using bis-phospholane ligands, such as Binapine, [16] TangPhos, [16] Ph-Bpe, [17] Esphos, [18] as well as bis-3,4-diazaphospholane [19] and bis-phosphonite ligands. [20] The first successful report concerning the synthesis of tetrahydrofuran-3-carbaldehyde 12 by Rh-catalysed asymmetric hydroformylation of 2,3-and 2,5-dihydrofurans was published by Nozaki in 1997 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…The chiral ligands chosen for initial studies on the hydroformylation of dimethylacrylamide were (R,R)-PhBPE, [13] (R,R)-Chiraphite, [7,10] (R,R)-Kelliphite, [7,8] the phosphine-phosphite ligands denoted POP, [14] while later studies used the (S,S,S) or (R,R,S)-Diazaphos-SPE ligand, developed by Landis and co-workers [12] (see Figure 1). The ligand to Rh ratio was 1.25:1, since in many many experiments with a wide variety of alkenes, we have observed that ratios of 1.1-1.5 generally give the best results.…”
Section: Resultsmentioning
confidence: 99%
“…This corresponds to the same sense of enantioselection as has been observed in the asymmetric hydroformylation of vinyl acetate using this ligand (styrene also hydroformylates on the same face of the alkene, although the configuration changes due to the priority rules). [12] The N,N-diisopropylamine derivative, 6, was found to be hydroformylated more slowly, but with similar levels of enantioselectivity as the dimethyl analogue (Table 3, runs 7-13). The N,N-diisopropylacrylamide was also found to racemise at a similar rate to the N,N-dimethyl analogue, a drop in ee of 56% to 38% was noted upon standing in CDCl 3 over 24 h. The l-valine methyl ester-derived imine of this substrate was found to be more configurationally stable in chlorinated solvents with no drop in ee upon standing for 24 h in CDCl 3 .…”
Section: A C H T U N G T R E N N U N G (Sss)-3mentioning
confidence: 95%